2020
DOI: 10.1021/acsnano.9b08136
|View full text |Cite
|
Sign up to set email alerts
|

Realization of Symmetry-Enforced Two-Dimensional Dirac Fermions in Nonsymmorphic α-Bismuthene

Abstract: Two-dimensional (2D) Dirac-like electron gases have attracted tremendous research interest ever since the discovery of free-standing graphene [1-3]. The linear energy dispersion and non-trivial Berry phase play the pivotal role in the remarkable electronic, optical, mechanical and chemical properties of 2D Dirac materials [4]. The known 2D Dirac materials are gapless only within certain approximations, for example, in the absence of SOC. Here we report a route to establishing robust Dirac cones in 2D materials… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 34 publications
2
62
1
Order By: Relevance
“…In contrast, the surface buckling was found to be one order of magnitude smaller for Bi(110) islands on the HOPG substrate. Kowalczyk et al: reported the buckling was smaller than 0.004 � 0.0005 nm [36]. The BP-like Bi(110) islands with a thickness of 2 ML (= 1 BL) on the HOPG substrate were observed to display gapless states at the edge, as expected for a 2D topological insulator [30].…”
Section: Nucleation and Growth Of Bi(110) Filmsmentioning
confidence: 87%
See 1 more Smart Citation
“…In contrast, the surface buckling was found to be one order of magnitude smaller for Bi(110) islands on the HOPG substrate. Kowalczyk et al: reported the buckling was smaller than 0.004 � 0.0005 nm [36]. The BP-like Bi(110) islands with a thickness of 2 ML (= 1 BL) on the HOPG substrate were observed to display gapless states at the edge, as expected for a 2D topological insulator [30].…”
Section: Nucleation and Growth Of Bi(110) Filmsmentioning
confidence: 87%
“…In this respect, the results do not contradict the findings of Lu and co-workers. In a recent experiment, the Bi(110) film on the graphite substrate was reported to have an extremely small buckling less than 0.004 � 0.0005 nm [36]. [51], and icosahedral Al-Pd-Mn quasicrystals [52].…”
Section: Ultrathin Bi(110) Filmsmentioning
confidence: 99%
“…Although a large number of 2D Dirac semimetals have been proposed, the Dirac cones in these materials are protected by point symmetry operations. So far, the 2D nonsymmorphic Dirac semimetals are rarely reported in the literature, including the HfGeTe family, [47] X 3 SiTe 6 (X ¼ Ta, Nb), [48] α-bismuthene, [49] and MX (M ¼ Sc, Y; X ¼ S, Se, Te). [50] Unfortunately, only α-bismuthene has been experimentally confirmed to be a Dirac semimetal.…”
Section: Introductionmentioning
confidence: 99%
“…Square LG 64 supports Dirac cones at X and S only in the presence of SO interaction; this is confirmed by DFT band structure of MX compounds (M = Sc, Y; X = S, Se, Te)[39] as well as in X point (S point was not discussed since the corresponding energies are too far from the Fermi level) in ARPES experiments and DFT calculations in synthesised layered 3D ZrSiS[40] and numerically in monolayer HfGeTe[41]. Experimentally synthesised α-Bismuthene belongs to LG 42 and hosts spinfull Dirac cones at X and Y points, as confirmed by micro-ARPES technique and DFT calculations[42].Among already reported structures with PF or FT dispersions are monolayer GaXY(X = Se, Te; Y = Cl, Br, I), with non-centrosymmetric symmetry LG 32 providing SO caused Dirac cones at X point and PF at Y point. Indeed, fourfold degeneracy at Y point (called Dirac point in…”
mentioning
confidence: 77%